Anteseden Keputusan Penggunaan Bank Digital pada Generasi Z di Jabodetabek - Muhamad Ilham; Umi Widyastuti; Diena Noviarini (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to analyze the influence of Financial Literacy, Friend Influence, Perceived Ease of Use, and Perceived Enjoyment on the Decision to Use digital banking among Generation Z in Greater Jakarta. The research employs a quantitative method using a survey technique through an online questionnaire. The sample consists of 144 respondents aged 13–28 years who reside in Greater Jakarta and have digital bank accounts. Data analysis was conducted using the Partial Least Squares Structural Equation Modeling (PLS-SEM) technique through SmartPLS 4 software. The results show that Financial Literacy has a significant positive effect on the Decision to Use. Friend Influence is also proven to have a significant positive effect on the Decision to Use. Furthermore, Perceived Ease of Use has a significant positive effect on Perceived Enjoyment, and Perceived Enjoyment has a significant positive effect on the Decision to Use. The findings are expected to provide theoretical contributions to the development of technology adoption models as well as practical contributions to the banking industry in formulating appropriate marketing strategies to increase digital bank usage among young generations. The implications of this study indicate that digital banking service providers need to develop strategies that focus not only on application usability but also on improving digital financial literacy, creating enjoyable user experiences, and leveraging social influence to encourage digital bank usage decisions among Generation Z.